Counterintuitive response to tax incentives? Mortgage interest deductions and the demand for debt - Dag Einar Sommervoll (Statistics Norway, Research Department, 2007)
A number of European countries changed their tax system in the early 1990s along the lines of the US tax reform act of 1986. After the reforms marginal tax rates were generally lower, and mortgage interest deductions less generous. At the same time a long period of house appreciation started in most countries. This paper considers this puzzle empirically using a rich data base of Norwegian tax records from 1986 to 2000. We use nonparametric, difference in difference and tobit approaches in attempt to control for a wide array of factors that may offset, or mask, response to changed incentives. Of special concern is possible credit constrains as implied by credit score models routinely applied by credit institutions. We find a surprisingly static relationship between the probability of debt across age groups, and a strikingly linear and unchanged relationship between debt and gross income for young households. After the reform house prices doubled and tripled. The wealth effect may spur consumption. We find no sign of consumption smoothing by using self-owned housing as debt collateral, not even for older households. On the contrary, older households did react to the reform by reducing real debt.
Keywords: D91; H20; 330; Tax incentives; credit rationing; mortgage market; household debt